Valorization of the chemical diversity of the tropical red seaweeds Acanthophora and Kappaphycus and their applications in aquaculture: A review - Guillén, Paúl O.; Motti, Pierfrancesco; Mangelinckx, Sven; De Clerck, Olivier; Bossier, Peter; Van Den Hende, Sofie (Frontiers in Marine Science, 2022)
Seaweeds play an important role in marine ecology due to their oxygen production, and carbon dioxide and nutrient capture, amongst other functions. They are also an important driver in the development of the blue bioeconomy due to the vast diversity of unique chemicals with a broad range of industrial and biotechnological applications. In tropical regions, the seaweed production has been focused on only a few species, mainly the red seaweed Kappaphycus spp., due to their fast growth rate and high specific polysaccharide content use in the food industry. There is a strong need to develop new applications of these red seaweed species in other promising sectors. The aquaculture sector has shown rapid growth in recent years, due to the increasing demand for seafood. Furthermore, to diversify the culture of red seaweeds, more tropical species need to be commercialized. Acanthophora spp., seem to be a promising candidate, as they are edible red seaweeds which are naturally abundant in several tropical countries. To investigate the technical potential for applications of their biomass and high added-value bioproducts in aquaculture, this study reviews the characterization and valorization of biochemicals of Kappaphycus spp. and Acanthophora spp. and identifies related research gaps. The wide chemical diversity (polysaccharides, phytohormones, pigments, amino acids, and pigments) has led to research on a wide range of applications for aquaculture, including pathogen control, immunostimulant, antioxidant, bioremediation, feed, UV protectants, increase in seafood shelf life, animal colorant, and growth regulator for microalgae culture. This study will contribute to boosting their applications in the aquaculture sector and, by this, helping stakeholders to benefit from these two red seaweeds by contributing to the diversification of the blue bioeconomy in tropical countries.